8-Methoxypsoralen disrupts MDR3-mediated phospholipids efflux and bile acid homeostasis and its relevance to hepatotoxicity. (1st July 2017) - Zhao, Guolin; Xu, Dengqiu; Yuan, Ziqiao; Jiang, Zhenzhou; Zhou, Wang; Li, Zhijian; Yin, Mengyue; Zhou, Zhixing; Zhang, Luyong; Wang, Tao
Graphical abstract: Abstract: Since its discovery in 1987, multidrug resistance 3 P-glycoprotein (MDR3) had recognized to play a crucial role in the translocation of phospholipids from the inner to outer leaflets of bile canalicular membranes. An increasing number of reports suggest that drug-mediated functional disruption of MDR3 is responsible for drug-induced cholestasis. 8-Methoxypsoralen (8-MOP) is used clinically to treat psoriasis, vitiligo and other skin disorders. However, psoralens safety for long-term use is a concern. In the current study, we evaluate 8-MOP's potential hepatotoxicity and effects on bile formation. Sprague Dawley (SD) rats were treated daily 200 mg/kg or 400 mg/kg of 8-MOP orally for 28 days. The result showed a prominent decrease in biliary phospholipids output, which associated with the down-regulation of MDR3. Elevated bile acid serum level and increased biliary bile acid outputs were observed in 8-MOP-treated groups. The disturbance of bile acid homeostasis was associated with changes in enzymes and proteins involved in bile acid synthesis, regulation and transport. Human liver cell line L02 was used to determine on the mRNA and protein levels of MDR3. Cells treated with 8-MOP reveled a decrease in fluorescent PC (phosphatidylcholine) secretion into the pseudocanaliculi (formed between adjacent cells) compared with untreated cells. Our investigation represent the first evidence that 8-MOP can induce cholestatic liver injury by disturbing MDR3-mediated phospholipids efflux and bile acid homeostasis.